IMPLEMENTATION OF THE CPM METHOD IN THE CONSTRUCTION PROJECT OF THE SURABAYA “X” HOSPITAL HEALTH CHECKUP - Hendry Apriyanto; I made Jiwa Astika; Eko Krisdiono (Indonesian Naval Technology College STTAL, 2022)
The process of planning to project control during the execution of construction work is an important activity of aproject. A project can be said to be a success or a failure caused by ineffective planning and control, so projectactivities fail. so there will be a delays, decreased quality, and increased implementation costs. A project is limitedby a predetermined time and cost so management in the project must be able to anticipate changing conditionsthat occur. The Critical Path Method abbreviated CPM method can be applied to manage project completion timemore efficiently and effectively. To be able to reduce the impact of project delays and cost overruns through acrash calculation mechanism with three alternative controls; additional labor or overtime work. Durationacceleration is carried out on jobs that are on the critical path and with the cheapest costs. In this study, the totalproject age was 277 calendar days, while the project deadline was 284 calendar days, thus the project wasdelayed for 7 calendar days with a total fine of Rp 25.242.944.400 and penalty cost is 1/1.000 for sum of contract.In this study the CPM method is intended to shorten the life of the project so that it can be completed in accordancewith the predetermined time limit and determine the age of project in accordance with the existing contract, usingCPM the project life can be shortened to 257 working days with an budget efficiency Rp. 176,700,611Keywords: Scheduling, CPM, Critical Path, Crashing, Time Acceleration